Parallel Dimensions of Knowledge: Bibliometric Insights into Metaphysics, Culture, and Modern Physics (2020-2025) - Rahmatta Thoriq Lintangesukmanjaya; Dwikoranto Dwikoranto; Ilmiawan Hakim (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to analyze research trends on the concept of parallel worlds within metaphysical studies and its connections to both modern and classical physics. The focus is on exploring the relationship between metaphysical perspectives, cultural traditions, and scientific theories such as relativity, dimensions, and thermodynamics. Method: This research adopts a descriptive qualitative approach using a Systematic Literature Review (SLR) and bibliometric analysis. Data were collected from various international academic databases covering publications from the last five years and were analyzed thematically to identify patterns, conceptual linkages, and emerging research trends. Results: The analysis reveals a growing number of publications discussing parallel worlds and metaphysics over the past five years. Many studies integrate traditional and cultural wisdom with modern physics, positioning the field as a multidisciplinary endeavor bridging philosophy and science. Novelty: This study finds that parallel worlds are closely connected to metaphysics and physics, particularly in the context of space-time dimensions, relativity, quantum mechanics, and thermodynamic principles. The integration of cultural, philosophical, and scientific perspectives highlights that metaphysics is not solely speculative but can be examined scientifically through interdisciplinary approaches.